2015
DOI: 10.1186/s12873-015-0063-0
|View full text |Cite
|
Sign up to set email alerts
|

A majority of rural emergency departments in the province of Quebec use point-of-care ultrasound: a cross-sectional survey

Abstract: BackgroundPoint-of-care ultrasound (POCUS) can be used to provide rapid answers to specific and potentially life-threatening clinical questions, and to improve the safety of procedures. The rate of POCUS access and use in Canada is unclear. The objective of this study was to examine access to POCUS and potential barriers/facilitators to its use among rural physicians in Quebec.MethodsThis descriptive cross-sectional study used an online survey. The 30-item questionnaire is an adapted and translated version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 25 publications
3
47
0
2
Order By: Relevance
“…16 In stark contrast to Ontario and Newfoundland, a survey of rural ED physicians in Quebec by Léger et al in 2014 revealed that PoCUS was available in 95% of rural EDs. 17 Variable access to bedside ultrasound in rural EDs also exists in the United States. One survey of ED directors in Colorado, Georgia, Massachusetts, and Oregon reported that only 39% of rural EDs had access to bedside ultrasound.…”
Section: Lack Of Equipmentmentioning
confidence: 99%
See 2 more Smart Citations
“…16 In stark contrast to Ontario and Newfoundland, a survey of rural ED physicians in Quebec by Léger et al in 2014 revealed that PoCUS was available in 95% of rural EDs. 17 Variable access to bedside ultrasound in rural EDs also exists in the United States. One survey of ED directors in Colorado, Georgia, Massachusetts, and Oregon reported that only 39% of rural EDs had access to bedside ultrasound.…”
Section: Lack Of Equipmentmentioning
confidence: 99%
“…16 Léger et al discovered that 95% of respondents believed that PoCUS was essential for rural ED practice, but 24% of physicians did not use PoCUS on a regular basis with the most common reason for lack of use being limited access to training programs. 17 In the WWAMI region of the United States, 62% of surveyed rural physicians identified a lack of training as a barrier to PoCUS use, with 35% having difficulty with image interpretation. A majority of these physicians (80%) were interested in a PoCUS course if offered at their site with many (64%) also being interested in a distance learning program.…”
Section: Lack Of Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that 75% of rural ED physicians believed that POCUS was an essential tool and skill to master in rural EDs, but few physicians use it regularly. 41 Learning its use is difficult due to little access to continuing medical education.…”
Section: The Challengementioning
confidence: 99%
“…In parallel, POCUS' clinical implementation, as an extension of the physical exam in rural medicine is steadily increasing (33). This is reflected by the recent surge of generalist/specialist and rural health care facilities purchasing POCUS equipment (34)(35)(36). Thus, with limited access to other formal imaging diagnostic modalities, POCUS has become an attractive ally to rural medicine.…”
Section: Rurality and Pocusmentioning
confidence: 99%